The use of reperfusion and revascularization procedures in acute coronary syndrome in Portugal: a systematic review - Lopes-Conceição, L (2014)
Introduction and Objectives: Reperfusion and revascularization therapies play an important role in the management of coronary heart disease and have contributed to decreases in case fatality rates. We aimed to describe the use of these therapies for the treatment of acute coronary syndrome (ACS) patients over time in Portugal. Methods: PubMed was searched in July 2012. The proportion of patients treated with fibrinolysis, primary percutaneous coronary intervention (PCI), any PCI and coronary artery bypass grafting (CABG) was described according to type of ACS: STEMI (≥90% patients with ST-segment elevation or Q-wave myocardial infarction), NSTE-ACS (≥90% patients with non-ST-segment elevation ACS) and mixed ACS (all others). Results: We identified 41 eligible studies, published between 1989 and 2011. Twenty-eight reported on samples considered representative of ACS patients treated in Portugal. The small number of estimates of the use of each treatment in STEMI and NSTE-ACS patients precluded identification of any time trend. In the last 20 years, the proportion of mixed ACS patients treated with fibrinolysis decreased and the use of PCI increased, while the use of CABG did not change. Conclusions: The general pattern of the use of reperfusion and revascularization is in accordance with that reported in other developed countries, reflecting a favorable trend in the quality of care of ACS patients. The relatively small number of estimates on the same procedure in comparable patients limits the generalizability of the conclusions, and highlights the need for systematic approaches to monitor the use of treatments over time.